Heritage Interpretation: Framework for a New Understanding of Cities - Time, Laura Alexandra (MAJ - Malaysia Architectural Journal, 2025)
Cities are complex structures embodying a series of site specific conflicts. Problems like overtourism, gentrification, pollution, perceptions of multiculturalism and diversity are issues that require architects and urban planners to become agents of change. From within the profession, we are becoming increasingly aware of the importance of community participation in our work, along with stewardship for all heritage. At the same time, UNESCO (2020) is acknowledging the role of heritage interpretation: a field that turns heritage into a present-day meaningful experience. An interpretive perspective supports cooperation between stakeholders through an analysis of the interplay of physical spaces, societal constructs, and human actions. To this respect, a collaboration started between UNESCO and the European Association for Heritage Interpretation - Interpret Europe (IE) for offering training programmes at World Heritage Sites (WHS) in Europe. Endorsing universally shared values and in alignment to the UN sustainable development goals, value-based heritage interpretation facilitates not only communication to the people around a site (visitors as well as locals), but more importantly understanding and active participation. This paper introduces basic principles of heritage interpretation (HI) and research findings in the field, in order to explore how interpretive planning (IP) can become a tool for understanding and mediating a city’s dynamics while influencing the reception of space and policies in the urban environment. It will make use of recent examples in changing frames at heritage sites and connect them to a developing case study for the city of Sinaia (Romania) that underscores the complexity of urban settlements and the need for a transdisciplinary approach.